"As vast as the world"—reflections on A Very Easy Death by Simone de Beauvoir. Issue 2 (6th December 2004) - Brennan, F
Abstract : In 1964, Simone de Beauvoir, arguably one of the greatest writers of 20th century Europe, published an account of the final 6 weeks of her mother's life. It is a beautifully written, raw, honest, and powerful evocation of that period from the viewpoint of a relative. Its themes are universal—love, ambivalence in family ties, loss, and bereavement. Given that the events preceded the modern palliative care movement, reflections are made on differences in medical practice since the book's publication.